Weak states and successful elites: Extraversion strategies in Africa - Denis Tull (Stiftung Wissenschaft und Politik (SWP), 2011)
Ever since the terror attacks of 11 September 2001, Western states have identified security problems in Sub-Saharan Africa no longer as purely regional issues, but as international challenges as well. As a result, the EU and its member states and the USA have considerably expanded their attempts to tackle security-related challenges in Africa. Focus has been placed on the prevention and resolution of conflict, political institution and good governance reforms, state building, and combating terrorism. The results of these policies have often failed to meet expectations. In some situations, the objectives have proven to be too ambitious, while in others, Western policies have suffered from shortcomings of their own making. An additional factor, however, is often paid insufficient attention: the attitudes and behaviour of the very governments and political elites that rule weak states. These actors, indiscriminately called "partners" because Western actors rely on their cooperation, often do not share the interests of their external supporters. This report examines how the governments of externally dependent crisis states engage with Western policy prescriptions. Which strategies do local elites employ to shape Western policies in an effort to make them compatible with their own political interests? Three examples of Western efforts to reform fragile states in Africa are presented. They concern fairly typical Western security policies and how these are "successfully" handled by ruling elites in African states: crisis and conflict prevention in Chad, security sector reform in DR Congo, and counter-terrorism in Uganda. The report shows how Western policies towards Africa's crisis-ridden states run the risk of being used as instruments of local government elites. They can fail in their objectives (as in Congo and Chad) or have unexpected consequences, which present new problems such as authoritarian tendencies and increased levels of corruption (as in Uganda). The fact that such states are politically and economically dependent on Western donors does not foster political change if local elites see it as a threat to their power
Keywords: 320